2022
DOI: 10.1038/s41598-022-26338-0
|View full text |Cite
|
Sign up to set email alerts
|

Fig latex inhibits the growth of pathogenic bacteria invading human diabetic wounds and accelerates wound closure in diabetic mice

Abstract: Impaired wound healing is one of the most critical complications associated with diabetes mellitus. Infections and foot ulcers are major causes of morbidity for diabetic patients. The current treatment of diabetic foot ulcers, commonly used antibiotics, is associated with the development of bacterial resistance. Hence, novel and more effective natural therapeutic antibacterial agents are urgently needed and should be developed against the pathogenic bacteria inhabiting diabetic wounds. Therefore, the current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 115 publications
0
6
0
Order By: Relevance
“…9-Hexacosene and dodecanoic acid, dodecyl ester, which only identified on 75% FC, have analgesic, anti-inflammatory [24], and antiseizure [25] activities. 2,5-dihydroxybenzoic acid has antibacterial, antiviral, neurological effect, antiatherosclerotic, antifibrotic, anti-ageing, anti-ulcer, and anticancer activities [26], and lanosta-8,24dien-3-one has anti-fungal activities [27] identified that only on 70% FC. Dotriacontanal, nonadecyl trifluoroacetate, and octacosanal have only detected on 55% FC.…”
Section: Discussionmentioning
confidence: 99%
“…9-Hexacosene and dodecanoic acid, dodecyl ester, which only identified on 75% FC, have analgesic, anti-inflammatory [24], and antiseizure [25] activities. 2,5-dihydroxybenzoic acid has antibacterial, antiviral, neurological effect, antiatherosclerotic, antifibrotic, anti-ageing, anti-ulcer, and anticancer activities [26], and lanosta-8,24dien-3-one has anti-fungal activities [27] identified that only on 70% FC. Dotriacontanal, nonadecyl trifluoroacetate, and octacosanal have only detected on 55% FC.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic patients’ immune systems are substantially weaker than those of healthy individuals. Therefore, the presence of infection in diabetic patients is a serious and fatal problem that can potentially result in limb loss 39 . Past research findings reveal that a variety of bacteria, including S. aureus , 40 E. coli , 41 and P. aeruginosa 42 frequently infect diabetic wounds.…”
Section: Diabetic Foot Ulcermentioning
confidence: 99%
“…Therefore, the presence of infection in diabetic patients is a serious and fatal problem that can potentially result in limb loss. 39 Past research findings reveal that a variety of bacteria, including S. aureus , 40 E. coli , 41 and P. aeruginosa 42 frequently infect diabetic wounds. These microbes cause the progression of sepsis and life‐threatening infections by penetrating deeper into the fascia via irritated or poorly perfused skin.…”
Section: Diabetic Foot Ulcermentioning
confidence: 99%
“…The infection of pathogenic bacteria seriously affects human health and life, and postoperative infections have a high mortality rate, which frequently occurs worldwide. , Clinical bacterial infections are usually treated with antibiotic drugs, which have made significant contributions to basic medical research and social development, and are indispensable in global healthcare systems . Unfortunately, the overuse of antibiotics has led to increasing bacterial resistance, which poses a serious threat to the treatment of bacterial infections. Thus, it is urgent to develop new bactericidal strategies that do not involve antibiotics.…”
Section: Introductionmentioning
confidence: 99%